Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.5812/asjsm.23129
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Epidemiology of Traumatic Injuries in 19000 Adults: a 5-Year-Study in a Tertiary Trauma Center in Iran

Abstract: Background:Basic epidemiological data can provide estimates when discussing disease burden and in the planning and provision of healthcare strategies. There is little quantitative information in the literature regarding prevalence of traumatic injuries from developing countries.Objectives:The aim of the current preliminary study was to reveal the prevalence and age and gender distribution of various traumatic injuries in a tertiary referral orthopedic hospital in Iran.Patients and Methods:In a prospective desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
5
17
0
Order By: Relevance
“…The male gender was the most recurrent one, corresponding to 60% of the total and to high prevalence of these disorders in the age group between 20 and 49 years. This was similar to Mehrpour et al 20 , who identified a higher prevalence in males, whose most frequent issue was bone fracture.…”
Section: Discussionsupporting
confidence: 90%
“…The male gender was the most recurrent one, corresponding to 60% of the total and to high prevalence of these disorders in the age group between 20 and 49 years. This was similar to Mehrpour et al 20 , who identified a higher prevalence in males, whose most frequent issue was bone fracture.…”
Section: Discussionsupporting
confidence: 90%
“…For Berecki Gisolf-J [10] fractures of finger/toe, arm and the ankle are the most common. Like us, Mehrpour SR in Iran [7], ranks first bone fractures of the forearm. The prevalence of falls as a cause of fractures in our series reflects this allocation.…”
Section: Discussionmentioning
confidence: 93%
“…It helps to expand the initiative of trauma injury control and prevention in our area, build up new protocols of trauma management, facilitate our trauma centers, and utilize our resources more efficiently (1-3). …”
Section: Introductionmentioning
confidence: 99%